DEVELOPMENT OF THE ARMENIAN “BIG FIVE” QUESTIONNAIRE SHORT VERSION - Serobyan, A. K. (Modern Psychology, 2019)
In many psychological researches we need to use short versions of the personality traits questionnaires. The aim of the article is to present reliability and validity analysis of the short version of the Armenian Big Five Questionnaire, which measures only five main factors. Data from 323 students and non-students was used in the study (84.2% female, Mage=22.6, StDevage=5.726) The results show that the Cronbach’s alpha and test-retest coefficient for all the five scales has been obtained high enough that the questionnaire will be considered reliable. Besides a confirmatory factor analysis was conducted to reveal construct validity of the questionnaire. After describing psychometric procedures 30 of 40 preliminarily items left.